Pickering emulsifiers based on hydrophobically modified small granular starches Part II – Effects of modification on emulsifying capacity. (1st December 2018) - Marefati, A.; Matos, M.; Wiege, B.; Haase, N.U.; Rayner, M.
Highlights: Emulsifying capacity correlated with starch type and modification level. Emulsion stability was highest for quinoa followed by rice and then amaranth. Emulsifying capacity correlated with the protein content of the starch granules. Increasing modification level improved the performance of low protein starches. All emulsions with quinoa starch granules had superior gravitational stability. Abstract: Small granular starches from rice, quinoa, and amaranth were modified with octenyl succinic anhydride (OSA) at 5 defined intervals (0–3.0%) and investigated with respect to emulsifying capacity and stability. Starch granule surfaces were characterized by Brunauer–Emmett–Teller and contact angle measurements. Emulsifying capacity was characterized by multiple light scattering (MLS) and particle size analysis. Stability towards environmental stress was characterized by centrifugation and MLS. Surface hydrophobicity and emulsifying capacity correlated with starch type and modification level. Quinoa stabilized emulsions had the smallest droplet size (e.g. 59.2 μm at 3.0% OSA) and superior stability, both before and after centrifugation, especially at the lowest modification levels. Rice and amaranth had larger droplets (99.8 and 84.1 μm at 3.0% OSA respectively). Amaranth, despite its small size showed poorer performance than quinoa, especially at lower modification levels. The higher emulsifying efficiency of quinoa starch granules attributed to the higher protein content.